2014
DOI: 10.2754/avb201483030187
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the serum protein electrophoretic pattern in lambs during the first month of life

Abstract: Studies of the changes in serum protein pattern in the neonatal period in animals are still limited. Therefore, the objective of this study was to evaluate the changes in the concentrations of serum protein fractions in 7 clinically healthy merino lambs (4 males, 3 females) during their first month of life. The first blood sampling was performed before the colostrum intake and then at 1, 2, 7, 14 and 30 days of age. Blood serum was analysed for total serum protein concentrations and for the relative and absolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 17 publications
7
9
0
Order By: Relevance
“…From day 2 the values of A/G subsequently increased to the 14th day of life. These findings correspond with results reported by Šlosárková et al (2014) and Tóthová et al (2015) in calves and by Nagy et al (2014) in lambs. In contrast to these findings Piccione et al (2011bPiccione et al ( , 2013 reported a subsequent decrease of A/G in comissana lambs and goat kids from the first day after birth to the 13th day of life.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…From day 2 the values of A/G subsequently increased to the 14th day of life. These findings correspond with results reported by Šlosárková et al (2014) and Tóthová et al (2015) in calves and by Nagy et al (2014) in lambs. In contrast to these findings Piccione et al (2011bPiccione et al ( , 2013 reported a subsequent decrease of A/G in comissana lambs and goat kids from the first day after birth to the 13th day of life.…”
Section: Discussionsupporting
confidence: 93%
“…In our study the highest mean concentrations of TP were observed 24 h after birth in calves and lambs. Similar results were reported by Šlosárková et al (2014) in dairy calves and Nagy et al (2014) in lambs. A different dynamics of TP concentration was observed in goat kids; the values progressively increased from the 0th to the 4th sampling.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An increased serum and plasma level of this protein has been reported following pathologic conditions. Plasma Hp concentration have been reported in the past to cause no significant effect on gender, pregnancy, lactation status, or age of an animal [14] but recently many researchers reported that acute phase proteins including the serum haptoglobin concentration is influenced by age, growth and development in goats and other ruminant animals [15,16]. Hp is deemed a major positive acute phase protein in ruminants as its concentration rises more than 10 times in response to the stimulation [17].…”
Section: Introductionmentioning
confidence: 99%
“…Acute phase proteins (APP) are reactants synthesized during an acute phase response to several stimuli such as infection, inflammation, stress, trauma, tissue damage or neoplasia (Pyorala 2000; Murata et al 2004;Petersen et al 2004;Tothova and Kovac 2009;Tothova et al 2014). Moreover, several physiological factors affect serum protein concentrations, including the species and breed, age, hormones, sex, pregnancy, colostrum and milk intake, lactation, temperature, season and seasonal rhythms (Shaffer et al 1981;Krajnicakova et al 2003;Batavani et al 2006;Thomas 2006;Balikci et al 2007;Eckersall 2008;Piccione et al 2010;Janku et al 2011;Piccione et al 2011a;Piccione et al 2012;Nagy et al 2014a;Nagy et al 2014b;Tothova et al 2014;Nagy et al 2015). In addition, serum protein concentrations are affected also by the storage duration of blood serum samples and the refrigerator temperatures (Tothova et al 2012a).…”
mentioning
confidence: 99%